Iron Overload in Patients With Heavily Transfused Sickle Cell Disease—Correlation of Serum Ferritin With Cardiac T2* MRI (CMRTools), Liver T2* MRI, and R2-MRI (Ferriscan®) - Alkindi, Salam; Panjwani, Vinodh; Al-Rahbi, Sarah; Al-Saidi, Khalid; Pathare, Anil V. (Frontiers in Medicine, 2021)
The treatment sickle cell disease (SCD) is mainly supportive, with blood transfusion forming the cornerstone. However, this results in alloimmunization, iron overload and hemolytic reactions. Serum ferritin (SF) it is notoriously unreliable, as a tool for iron overload assessment, since it is an acute phase reactant. This study aims to evaluate iron overload in SCD patients on chronic blood transfusions and specifically, correlate SF, with the current standard of care of iron overload assessment using MRI based imaging techniques. Amongst a historic cohort of 58 chronically transfused SCD patients, we were able to evaluate 44 patients who are currently alive and had multiple follow-up testing. Their mean age (range) was 35 (20-64) years and comprised of 68.2% female. Chronic blood transfusions were necessary for severe vaso-occlusive crisis (38.6%), severe symptomatic anemia (38.6%), past history of stroke (15.9%) and recurrent acute chest syndrome (6.9%). 14 (24%) patients among the original cohort died following SCD related complications. Amongst the patients currently receiving chelation, 26 (96%) are on Deferasirox (Jadenu® (24), or Exjade® (2)), with good compliance and tolerance. However, one patient is still receiving IV Deferoxamine, in view of the significantly high systemic iron burden. The mean SF reduced marginally from 4,311 ng/ml to 4,230 ng/ml, mean Liver T2* MRI dropped from 12 to 10.3 mg/gm dry weight, while the mean cardiac T2*MRI improved from 36.8 to 39.5 ms. There was a mild to moderate correlation between baseline and final values of SF ng/ml, r=0.33, p=0.01; Cardiac T2* MRI ms, r=0.3, p=0.02 and Liver T2* MRI mg/kg dry weight, r=0.6, p<0.001. Overall, there was a positive correlation between SF and Liver T2* MRI (Pearson’s r=0.78, p<0.001). Cardiac T2*MRI increased with the decreasing SF concentration, showing a negative correlation which was statistically significant (Pearson’s r=-0.6, p<0.001). Furthermore, there also was an excellent correlation between SF ng/ml and LIC by FerriScan© R2-MRI mg/g or mmol/kg (Spearmen’s rho - 0.723, p<0.008) in a small subset of patients (n=14) who underwent the procedure. In conclusion, our study demonstrated a good correlation between serial SF and LIC by either Liver MRI T2* or by FerriScan© R2-MRI.